INFLUENCE OF FLOW RATE ON THE REMOVAL OF COPPER, LEAD AND NICKEL FROM SOLUTIONS IN ELECTRODIALYSIS PROCESS - Aytaç, Ersin; Altın, Süreyya (MATTER: International Journal of Science and Technology, 2017)
In electrodialysis (ED) of heavy metals such as copper, lead and nickel from solutions, one of the main operating parameter is the flow rate. The study focus on understanding the impact of different flow rates on removal efficiency, current efficiency, specific electrical energy consumption and removed amount of matter in mg. 70, 140 and 200 mL/min of flow rates has been applied to ED stack which has constant operating parameters of 0.05 M NaCl containing electrolyte solutions, 45 V of applied voltage, pH of 6 and dilute solutions with heavy metal concentrations of 2 mg/L. After 360 min. of ED process removal efficiencies of all types of metals has shown an increment trend. As an opposite effect, current efficiencies has been declined. When examining the removed amount of matter during process, parallel indications to removal efficiencies has been determined. Increasing flow rates has increased the amount of matter removed. Last findings on the removal of heavy metal depending on flow rates were specific electrical energy consumptions. Comparing flow rates of 70 and 200 mL/min, energy consumptions per mg of heavy metal removed has raised. These results clearly points out that flow rate of dilute and electrolyte solutions in EC has an alternating effect on process. Further researches can be done for improving the removal efficiency and lowering the electrical energy consumption depending on other operational parameters on electrodialysis.